PERTUMBUHAN DAN HASIL TANAMAN JAGUNG SEMI (Zea mays L.) DENGAN FREKUENSI PENYIRAMAN DANPUPUK ORGANIK CAIR URIN SAPI - Siska Siska; Hidayati Mas'ud (Fakultas Pertanian, Universitas Tadulako, 2022)
The study aimed to investigate the effect of watering frequency and concentrations of liquid organic fertilizer (LOF) derived from cow urine on the growth and yields of corn in Lolu village, Sigi Biromaru sub district of Sigi district during April – June 2020. The study used a two-factorial randomized block design, with the first factor being the frequency of watering (every day, every two days, and every three days), and the second factor being the concentration of LOF (no LOF, 150 ml LOF/l, 200 ml LOF/l, 250 ml LOF/l, 300 ml LOF/l, and 350 ml LOF/l). The study comprised 54 polybags with 18 treatment combinations, each treatment was repeated three times. The results showed that there was no interaction effect between the watering frequency and the LOF treatments on all observation parameters. The 350 ml LOF/l treatment showed better growth and yields for the corn plant particularly for the number of leaves, weight of cob per plant, and length of cob per plant.